2014
DOI: 10.1016/j.jpsychires.2014.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of patient selection and study characteristics on signal detection in placebo-controlled trials with antidepressants

Abstract: An increasing rate of antidepressant trials fail due to large placebo responses. This analysis aimed to identify variables influencing signal detection in clinical trials of major depressive disorder. Patient-level data of randomized patients with a duloxetine dose ≥ 60 mg/day were obtained from Lilly. Total scores of the Hamilton Depression Rating scale (HAM-D) were used as efficacy endpoints. In total, 4661 patients from 14 studies were included in the analysis. The overall effect size (ES), based on the HAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 45 publications
2
24
0
1
Order By: Relevance
“…The most consistent finding is that a low symptom severity at baseline is a strong predictor of the placebo response in schizophrenia, 24 psychosis, 26 children with autism, 27 obsessive-compulsive disorder, 30 attention-deficit hyperactivity disorder, 32 binge-eating disorder, 34 and depression, 19,37,3943,47,48 despite the fact that in three studies the opposite was reported for schizophrenia, 23 psychosis, 25 and attention-deficit hyperactivity disorder. 33 …”
Section: Patient-centred Factorsmentioning
confidence: 94%
See 2 more Smart Citations
“…The most consistent finding is that a low symptom severity at baseline is a strong predictor of the placebo response in schizophrenia, 24 psychosis, 26 children with autism, 27 obsessive-compulsive disorder, 30 attention-deficit hyperactivity disorder, 32 binge-eating disorder, 34 and depression, 19,37,3943,47,48 despite the fact that in three studies the opposite was reported for schizophrenia, 23 psychosis, 25 and attention-deficit hyperactivity disorder. 33 …”
Section: Patient-centred Factorsmentioning
confidence: 94%
“…Other factors identified only in some analyses to be associated with higher placebo effect were a high number of study visits 46,48 (but only in older children and adults) and a low level of industry support. 35 …”
Section: Study Design-based Factorsmentioning
confidence: 95%
See 1 more Smart Citation
“…This approach is often chosen to assign more patients to the active drug in a two-arm trial for ethical reasons or to test more drug dosages against placebo by adding more study arms. As noted early on (Diener et al, 1999), unbalanced randomization may increase the overall placebo response in RCTs, as shown in trials on depression (Papakostas and Fava, 2009;Sinyor et al, 2010;Mancini et al, 2014), schizophrenia (Woods et al, 2005;Mallinckrodt et al, 2010), and psychosis (Agid et al, 2013). It is, however, unclear whether this represents a specific effect in neuropsychiatric disorders, because it has not been observed in other conditions, such as IBS Elsenbruch and Enck, 2015).…”
Section: Influence Of Randomized Clinical Trial Characteristicsmentioning
confidence: 99%
“…El número de sesiones de seguimiento también parece provocar un impacto terapéutico positivo sobre la respuesta placebo, representando hasta el 40% de dicha respuesta (Posternak & Zimmernan 2007;Mancini, Wade, Perugi, Lenox-Smith & Schacht, 2014), por lo que se sugiere que el impacto terapéutico es acumulativo y proporcional. Este hecho indica que la respuesta placebo depende en gran medida de la atención y el cuidado recibido durante el curso de los ensayos clínicos.…”
Section: Resumen De Los Resultadosunclassified